Pemanfaatan Teknologi Dalam Pembelajaran Aktif (Active Learning) Untuk Meningkatkan Interaksi dan Keterlibatan Siswa - Depita, Teti (STAI Asy-Syukriyyah, 2024)
In today's digital era, the world is faced with rapid technological advances. It cannot be denied that education today is able to follow this, especially in implementing active learning. However, many schools still do not fully utilize technology. Moreover, currently there are many cases of students being less active, less interacting and involved during distance and face-to-face learning. So this research emerged to answer this problem by focusing on the use of technology in an effort to increase student interaction and involvement in distance and face-to-face learning. Apart from that, it also aims to determine the impact of using technology in active learning. The method used in this research is a qualitative method in the nature of a literature study where data is obtained through books and journals related to this research. The results of the research show that technology has a positive impact. Technology is able to increase interaction between students and students, student interaction with learning, students become more actively involved which will have an impact on student learning achievement which is effective in realizing active learning. Wise integration of technology in the context of active learning can increase student interaction and involvement, thereby facilitating the learning process so that educational goals are achieved and the quality of education increases.